Real‐World Data on the p.Gly17Val RHOA Mutation in Diagnosing T Follicular Helper Cell Lymphomas - Yuri Tsuboi; Keiichiro Hattori; Naoki Kurita; Yasuhito Suehara; Toru Nanmoku; Ryota Matsuoka; Ryota Ishii; Sakurako Suma; Kenichi Makishima; Yumiko Maruyama; Tatsuhiro Sakamoto; Takayasu Kato; et al. (Cancer Medicine, 2025)
ABSTRACT Background T follicular helper (Tfh) cell lymphomas, including their most prevalent form, angioimmunoblastic T‐cell lymphoma, frequently present with clinical symptoms, such as fever and rash, accompanied by substantial immune cell infiltration within the tumor microenvironment. These features often obscure the distinction between Tfh lymphoma and other autoimmune or inflammatory conditions. Notably, the p.Gly17Val RHOA (G17V) mutation is commonly associated with Tfh lymphomas, including angioimmunoblastic T‐cell lymphoma, suggesting that testing for the G17V mutation may serve as a valuable diagnostic tool. However, it remains unclear which patients would benefit the most from G17V mutation testing. Methods In this study, we retrospectively reviewed the medical records of 224 patients tested for the G17V mutation as part of routine clinical practice. Results We detected G17V in 17 patients. Among Tfh lymphoma cases, the sensitivity and specificity of the G17V test were 0.533 and 0.955, respectively. We further explored the association between G17V positivity and the clinical features of patients undergoing testing for the first time (n = 186). The G17V mutation was more frequent in patients presenting with lymphadenopathy in combination with fever or skin rash and elevated soluble interleukin‐2 receptor levels (p = 0.002). The median time from G17V test submission to results was 11.6 d shorter than that for pathological diagnosis (p = 0.0009). Conclusions Given the noninvasive nature of the G17V test, its rapid administration to appropriate patients is expected to enable faster and more efficient diagnosis of Tfh lymphomas compared with conventional methods.